Web-PACS for Multicenter Clinical Trials. - Hernandez, J.A (IEEE Transactions on information technology in biomedicine)
Medical information systems are not designed for clinical trials using clinical imaging. This paper presents a conceptual model for clinical trials based on medical imaging from two complementary points of view: a technical model and a business model. A Web information system (WIS) for supporting multicenter clinical trials has been designed to implement the proposed model. We show that our approach overcomes the actual limitations by facilitating medical image management in the context of clinical trials or cooperative research